Interaction profile of macitentan, a new non-selective endothelin-1 receptor antagonist, in vitro - Weiß, Johanna; Theile, Dirk; Rüppell, Maximilian Alexander; Speck, Tobias; Spalwisz, Adriana; Haefeli, Walter E. (European journal of pharmacology, 2013)
Macitentan is a new non-selective endothelin-1 receptor antagonist under development for the treatment of pulmonary arterial hypertension. Information on the potential for macitentan to influence the pharmacokinetics of concomitantly administered drugs by inhibition or induction of drug metabolising enzymes or drug transporters is sparse. We therefore studied the potential of macitentan to inhibit and induce critical targets of drug metabolism and drug distribution (transporters) in vitro. Induction was quantified at the mRNA level by real-time RT-PCR in LS180 cells and revealed that macitentan significantly induced mRNA expression of cytochrome P450 3A4 (CYP3A4), P-glycoprotein (P-gp, ABCB1), solute carrier of organic anions 1B1 (SLCO1B1), and uridinediphosphate-glucuronosyltransferase 1A3 (UGT1A9). By means of a reporter gene assay our study establishes macitentan as a potent activator of pregnane X receptor (PXR). Inhibition of drug transporters was evaluated by using transporter over-expressing cell lines and fluorescent specific substrates of the respective transporters and revealed that macitentan is an inhibitor of P-gp, breast cancer resistance protein (BCRP), SLCO1B1, and SLCO1B3. Using commercial kits macitentan was demonstrated to be a moderate inhibitor of CYP3A4 and CYP2C19. In conclusion our data provide a comprehensive analysis of the interaction profile of macitentan with drug metabolising and transporting enzymes in vitro. Although macitentan has a similar or higher potency for induction and inhibition of drug metabolising enzymes and transporters than bosentan, its low plasma concentrations and minimal accumulation in the liver suggest that it will be markedly less prone to drug-drug interactions than bosentan.
Gesehen am 28.10.2021